Penggunaan Metode Audiolingual pada Pembelajaran Maharah al-Kalam di Madrasah Tsanawiyah - Afifah Rohadatulaisi, Jihan; Susiawati, Iis; Hasyim Fanirin, Moch. (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The audiolingual method in learning maharah al-kalam is an effective method in helping students develop speaking skills appropriately, because the application of the audiolingual method emphasizes repetitive practice through correct sentence patterns. However, this method still has limitations in adjusting learning to different learning styles of students, as well as the lack of in-depth research related to its application when combined with learning technology to improve student learning outcomes optimally. The purpose of this study is to find out the use of audiolingual method in learning maharah al-kalam in class VIII MTs Ma'had Al-Zaytun in 2024, to find out the obstacles faced and how to overcome these obstacles. This research method uses a qualitative approach with data collection techniques through observation or observation, in-depth interviews with the head of the madrasah, 8th grade Arabic teacher, and 8th grade students as many as 12 students, and documentation. The results showed that the use of audiolingual method in learning maharah kalam class VIII at MTs Ma'had Al-Zaytun in the implementation process is carried out through three main stages: planning, implementation, and evaluation, which are adjusted to the characteristics of students. One of the main obstacles faced by students is the difficulty in translating new vocabulary, which has an impact on their ability to practice dialogue with improvisation appropriately. To overcome this obstacle, teachers need to help students understand the meaning of the expression by translating together before proceeding to the practice stage.